IDENTIFYING ORGANIZATIONAL FACTORS OF JOB SATISFATION: THE CASE OF ONE SERBIAN COMPANY - Janićijević, Nebojša; Kovačević, Panta; Petrović, Ivana (Economic Annals, 2015)
This paper presents the results of exploratory research, the objective of which was to identify organizational factors of job satisfaction. A stratified random sample of 1,488 employees from a Serbian company answered a specially designed questionnaire, which asked them to rate the importance of and their satisfaction with fifty job different aspects. The survey results were analysed by means of three factor analyses, firstly using the data on the importance of job aspects, secondly using the data on satisfaction with the job aspects, and thirdly using data on the gap between the importance and satisfaction ratings. By synthesizing the results of the three factor analyse, a total of six job satisfaction factors was obtained, three of which are identical to previously identified factors and can be found in job satisfaction theory, two of which are modifications of already identified factors, and one factor which is new in this field of research.